Machiavellian Personality, Commitment, and Self-Efficacy: Unraveling Whistleblowing Intentions in Accounting Students: Kepribadian Machiavellian, Komitmen, dan Efikasi Diri: Mengungkap Niat Melakukan Whistleblowing pada Mahasiswa Akuntansi - Azmiyanti, Rizdina; Suhartini, Dwi; Yunida Putri, Sofie (Indonesian Journal of Law and Economics Review, 2023)
This study investigates the relationship between commitment professionalism, Machiavellian personality, and whistleblowing intentions among accounting students, while examining self-efficacy as a moderating variable. Conducted on a sample of 200 7th-semester accounting students at Universitas Pembangunan Nasional "Veteran" Jawa Timur, the study employs a quantitative approach, using primary data collected through an online survey. Analysis with WarpPLS 7.0 reveals that high commitment and professionalism in accounting students can foster whistleblowing intentions without requiring high self-efficacy. Similarly, students with high Machiavellian personalities demonstrate whistleblowing motivation, independent of self-efficacy levels. These findings suggest that accounting students possess a heightened awareness of the importance of whistleblowing, which should be further nurtured through education and reinforcement of ethical principles in order to produce graduates with strong moral character and commitment to professional integrity.Highlights: Personality traits significantly impact whistleblowing intentions. Self-efficacy plays a crucial role in fostering ethical behavior. Enhancing ethical awareness is vital for shaping future accountants. Keywords: whistleblowing intentions, Machiavellian personality, commitment professionalism, self-efficacy, accounting students.